Economic Enfranchisement, Goal Setting, and Rural Development. (28th November 2022) - Hackett, Susan; Watson, Philip
Abstract: This analysis introduces a conceptual framework for economic enfranchisement and studies its effect on an individual's likelihood to set strong financial goals. A conceptual and empirical model is developed to investigate how economic enfranchisement influences an individual's likelihood to set a goal and the strength of that goal. The empirical analysis employs an ordered probit to account for the two-stage goal-setting and goal strength decision process. Results show that economic enfranchisement has a significant effect on an individual's likelihood to set financial goals where more enfranchised individuals are more likely to set strong goals than their disenfranchised counterparts.